Assessment of the inhibition performance of ZIF-8 on corrosion Mitigation of API 5L X65 steel in 3.5 wt% NaCl: Experimental and theoretical insight - M.A. Chidiebere; V.C. Anadebe; R.C. Barik (Journal of Materials Research and Technology)
The synthesis and application of ZIF-8 as an effective corrosion inhibitor for the corrosion of API 5L X65 steel in 3.5 wt% NaCl have been studied. The synthesized ZIF-8 was characterized using some surface probe approaches, which include field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), high-resolution transmission electron microscopy (HR TEM), and X-ray photoelectron spectroscopy (XPS), respectively. The results showed that ZIF-8 exhibited regular hexagonal and orthorhombic-shaped nanoparticles. An approximately 62% yield was achieved. Electrochemical studies such as open circuit potential (OCP), potentiodynamic polarization (PDP), and electrochemical impedance spectroscopy (EIS) were performed. The polarization results show that ZIF-8 is a mixed-type inhibitor, revealing a strong impact on both the anodic and cathodic polarization current values. The EIS studies reveal an increase in the charge transfer resistance upon the introduction of ZIF-8. The existence of a strong protective film adsorbed on X65 steel was recognized via XPS and FT-IR analysis. The highest inhibition efficiency value of 98.1% was recorded at a concentration of 0.120 wt% ZIF-8. Quantum chemical computations in the framework of DFT and molecular dynamic simulation were used to determine the reaction sites on the inhibitor, and as such, in-depth insight into the reaction mechanism was revealed.